The Effect of Using Virtual Laboratory with Laboratory Reality and Learning Style on Science Process Skills of Students - Nur Choiriyah; Ibut Priono Leksono; Ujang Rohman; Bambang Winartod (Budapest International Research and Critics University, 2022)
The laboratory as a place to carry out practical activities is no longer limited to the meaning of a real room that can be seen directly, but in its development many virtual laboratories have emerged that utilize digital technology in their use. This study is intended to determine the effect of using a virtual laboratory with laboratory reality, and learning styles on students science process skills. This study is designed using a factorial design where the research sample was taken from the population with cluster random sampling technique. The research sample amounted to 144 students in SMA Negeri 2 and 4 Probolinggo. The research instrument used tests to measure science process skills and questionnaires to determine students' learning styles. The results of the students' science process skills test are research data that were analyzed using the two-way ANOVA test which had previously met the prerequisite tests for normality and homogeneity. The result of this research is that Fcount = 15.018 with Sig . = 0.000 < 0.01 in the method used, while in the learning style section Fcount = 10.326 with Sig. = 0.000 < 0.01. The results of the two-way ANOVA test on the third hypothesis obtained Fcount = 5.301 with a Sig value. = 0.006 < 0.01. From these results, it can be concluded that the three hypotheses (Ho) are rejected and Ha is accepted, which means that there is an effect of using virtual laboratories and laboratory reality on science process skills. Likewise, learning styles have a significant influence on students' science process skills. Based on the results of the third hypothesis test, it is also concluded that there is an interaction effect between the use of virtual laboratories with laboratory reality and learning styles on students' science process skills.